Disparities of Access, Use, and Barriers to Seeking Health Care Services in Arizona. Issue 2 (16th December 2021) - Gallaway, Michael Shayne; Aseret-Manygoats, Teresa; Tormala, Wayne
Abstract : Background: Access to health care (HC) services is important for promoting and maintaining health, preventing and managing disease, reducing unnecessary disability and premature death, and achieving health equity for all persons. Objectives: We assess social indicators among people living in Arizona that are associated with access, use, and barriers to seeking HC services. Research Design: We analyzed data (n=8073) from the 2018 Behavioral Risk Factor Surveillance System (BRFSS) to describe demographic and health characteristics among persons by HC access and use, and for whom costs were a barrier to seeking care. Results: Among Arizona adults, 13.5% reported lacking HC coverage, 28.7% reported lacking a personal doctor, and medical costs were a barrier to seeking care for 14.1%. Arizonans aged 18–34 years or with a high school education or less more often reported lacking HC coverage, a personal doctor, or not visiting a doctor because of costs. Past year medical and dental checkups were less common among less educated (≤high school) and never married persons. Hispanic persons more often reported lacking HC coverage or not visiting a doctor because of costs, and less often reported past year dental checkups. Conclusions: BRFSS can be analyzed to identify and quantify unique HC disparities, and the findings can serve as the basis for improving HC in communities. Expansion of HC services and providers may be achieved, in part, through incentives for providers to work in designated health professional shortage areas and/or leveraging telehealth/telemedicine in rural and urban underserved communities.